Transforming Indonesian Washing Machines into Efficient Wind Generators: Mengubah Mesin Cuci Indonesia Menjadi Pembangkit Listrik Tenaga Angin yang Efisien - Putra , Ahmad Nurwanda Bawono; Firdaus, Rachmat (Indonesian Journal of Innovation Studies, 2024)
People's consumption of household electronic devices is increasing, leading to higher energy demand in Indonesia, with washing machines being a significant contributor. This study explores repurposing used washing machine dynamos into electricity generators for windmills. Researchers used an LG washing machine dynamo and N52 neo super magnets, testing pulley diameters of 12 cm, 15 cm, 18 cm, and 20 cm. Results showed that larger pulleys increased generator output, with a 20 cm pulley producing 26 volts, 1.3 amperes, and 2525 rpm. However, the efficiency was low at 8.69%, indicating a need for further optimization. This approach has potential for sustainable energy solutions and reducing electronic waste. Highlight: Repurpose Dynamos: Converts washing machines to windmill generators, reducing electronic waste. Efficiency Challenge: Larger pulleys improve output but efficiency is only 8.69%. Sustainable Impact: Offers potential for sustainable energy and lower household consumption. Keyword: household electronics, energy consumption, washing machine dynamo, windmill generator, sustainable energy